Romania - Building Institutions for Public Expenditure Management : Reforms, Efficiency and Equity - A Public Expenditure and Institutions Review - World Bank (Washington, DC, 2013)
This Public Expenditure and Institutions Review (PEIR) was undertaken at a critical juncture of public expenditure management in Romania. Following three years of economic decline, the economy began growing in 2000, reaching a real GDP growth rate of 5.3 percent in 2001. The Government thus defined an economic reform strategy, to move forward the banking system and enterprise privatization, contain fiscal deficit, and reduce central government expenditures, with further fiscal decentralization. The PEIR focuses on five areas: (i) Structure of central state budget; (ii) Fiscal decentralization; (iii) Social expenditure; (iv) Pension reform; and (vi) Military and defense sector budget. The PEIR presents a policy framework for enhancing the effectiveness of processing, and allocating public expenditures, to improve Treasury accounting, curbe budget ceilings by accumulating payment arrears, and, by subjecting foreign financed public investments to full budgetary scrutiny. By emphasizing accountability in the management of extra-budgetary funds, the PEIR places also a need for firmer financial foundations for health, and pension funds, as well as on reconsideration of the present education finance mechanisms. Finally, it takes a broader look towards the need to define more stable local government expenditure assignments, that clearly define local government's own functions, from delegated functions.